2005
DOI: 10.1105/tpc.105.034090
|View full text |Cite
|
Sign up to set email alerts
|

RiceUndeveloped Tapetum1Is a Major Regulator of Early Tapetum Development

Abstract: The tapetum, the innermost of four sporophytic layers in the anther wall, comes in direct contact with the developing male gametophyte and is thought to play a crucial role in the development and maturation of microspores. Here, we report the identification of rice (Oryza sativa) Undeveloped Tapetum1 (Udt1), which is required for the differentiation of secondary parietal cells to mature tapetal cells. T-DNA or retrotransposon Tos17 insertions in the Udt1 gene caused male sterility. The anther walls and meiocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
357
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 352 publications
(371 citation statements)
references
References 74 publications
7
357
2
5
Order By: Relevance
“…Some genes previously identified as critical for postmeiotic anther development were down-regulated in the ptc1 microarray data (Table I), including a Cys protease (OsCP1; Lee et al, 2004), a fatty acyl-CoA reductase homologous to Arabidopsis MS2 (Aarts et al, 1997), lipid transfer proteins (Osc4, OsC6, YY1, and Os09g0525500; Tsuchiya et al, 1992;Hihara et al, 1996), a stilbene synthase (YY2; Hihara et al, 1996), BURP domain-containing proteins (RA8 and OsRAFTIN; Jeon et al, 1999), a P450 family member (CYP704B2; , a ribosomeinactivating protein (RA39; Jeon et al, 1999), and the putative homolog of AtMYB103 (Higginson et al, 2003;Zhang et al, 2007). Consistent with the RT-qPCR analysis, PTC1 showed up-regulation in the ptc1 mutant (2.97-fold at stage 8, 5.49-fold at stage 9), whereas genes involved in early tapetal and pollen regulation, such as CYP703A3 (Aya et al, 2009), TDR (Li et al, 2006), UDT1 (Jung et al, 2005), and GAMYB (Kaneko et al, 2004;Liu et al, 2010; Table I), showed no significant change. To understand the regulatory role of PTC1, we grouped the 2,417 genes into four COG (for Cluster of Orthologous Groups of proteins) categories: I, information storage and processing (144 genes); II, cellular processes and signaling (363 genes); III, metabolism (551 genes); and IV, poorly characterized genes (1,359 genes; Fig.…”
Section: Ptc1 Is Preferentially Expressed In the Tapetum And Microsposupporting
confidence: 72%
See 3 more Smart Citations
“…Some genes previously identified as critical for postmeiotic anther development were down-regulated in the ptc1 microarray data (Table I), including a Cys protease (OsCP1; Lee et al, 2004), a fatty acyl-CoA reductase homologous to Arabidopsis MS2 (Aarts et al, 1997), lipid transfer proteins (Osc4, OsC6, YY1, and Os09g0525500; Tsuchiya et al, 1992;Hihara et al, 1996), a stilbene synthase (YY2; Hihara et al, 1996), BURP domain-containing proteins (RA8 and OsRAFTIN; Jeon et al, 1999), a P450 family member (CYP704B2; , a ribosomeinactivating protein (RA39; Jeon et al, 1999), and the putative homolog of AtMYB103 (Higginson et al, 2003;Zhang et al, 2007). Consistent with the RT-qPCR analysis, PTC1 showed up-regulation in the ptc1 mutant (2.97-fold at stage 8, 5.49-fold at stage 9), whereas genes involved in early tapetal and pollen regulation, such as CYP703A3 (Aya et al, 2009), TDR (Li et al, 2006), UDT1 (Jung et al, 2005), and GAMYB (Kaneko et al, 2004;Liu et al, 2010; Table I), showed no significant change. To understand the regulatory role of PTC1, we grouped the 2,417 genes into four COG (for Cluster of Orthologous Groups of proteins) categories: I, information storage and processing (144 genes); II, cellular processes and signaling (363 genes); III, metabolism (551 genes); and IV, poorly characterized genes (1,359 genes; Fig.…”
Section: Ptc1 Is Preferentially Expressed In the Tapetum And Microsposupporting
confidence: 72%
“…However, transcription factors involved in regulating early tapetal differentiation or sporopollenin synthesis, including GAMYB (Kaneko et al, 2004;Aya et al, 2009;Liu et al, 2010), UDT1 (Jung et al, 2005), TDR (Li et al, 2006), and CYP703A3 (Aya et al, 2009), showed no obvious change ( Table I), suggesting that they act upstream of PTC1 (Fig. 11).…”
Section: Comparison Of the Ptc1 Regulatory Role With Those Of Gamyb mentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies have aimed at characterizing gene expression during stamen development on a global scale by microarray analysis (Amagai et al, 2003;Cnudde et al, 2003;Honys and Twell, 2003;Zik and Irish, 2003;Wellmer et al, 2004;Jung et al, 2005;Pina et al, 2005). All of these studies led to the identification of genes with expression in stamens and, in some cases, analyzed specific successive developmental stages (such as during gametophyte development; Honys and Twell, 2004).…”
mentioning
confidence: 99%